2021
DOI: 10.20473/mgi.v16i2.124-129
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Peer Influence and Family Eating Habits on Healthy Food Choices in Overweight Adolescents in Surakarta

Abstract: Unhealthy eating habits among Indonesian occur not only in adults, but also in adolescents. Adolescence is a transitional period and most easily aff ected by the surrounding environment. Environmental infl uences such as peer infl uence and family eating habits are dominant factors for food they choose to consume. This study aimed at analyzing the relationship of peer infl uence and family eating habits on healthy food choices in overweight adolescents in Surakarta. It used observational study with cross secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(3 reference statements)
1
2
0
1
Order By: Relevance
“…This means that the more positive their peer groups are, the higher the probability of changing their behaviour. This agrees with what was reported by Risti et al (2021) as well as Chen and Antonelli (2020) in Indonesia and Italy, respectively. Other factors that may influence an individual's behaviour include perceived health benefits, the use of media as well as the advice given by health professionals (Verplanken and Orbell, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…This means that the more positive their peer groups are, the higher the probability of changing their behaviour. This agrees with what was reported by Risti et al (2021) as well as Chen and Antonelli (2020) in Indonesia and Italy, respectively. Other factors that may influence an individual's behaviour include perceived health benefits, the use of media as well as the advice given by health professionals (Verplanken and Orbell, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…In line with the different results of previous studies on portion size influenced by social and psychological contexts, we also found that most studies on eating behaviour apply behavioural measurements in experimental settings (such as in the US, UK, and the Netherlands) using behavioural measurement, lab-based experiments, observations, and online experiments (Baker et al, 2019;Hermans et al, 2012;Otterbring, 2018;Robinson et al, 2022;Ruddock, Long, et al, 2021). However, in Indonesia, there has been a heavy reliance on subjective measurements, including self-reporting, surveys and FGD (Dewanti et al, 2022;Habibie et al, 2019;Risti et al, 2021), yet few studies have used behavioural measurements of food choices and portions. Indeed, behavioural measurement studies provide observable data without requiring participants to report their inner states.…”
Section: Introductionmentioning
confidence: 53%
“…Personal factors such as impression management are thought to also contribute to food choices when eating with others. Many studies have revealed that eating with familiar people tend to be excessive than with unfamiliar people (Habibie et al, 2019;Risti et al, 2021;Ruddock, Long, et al, 2021). However, even with an unfamiliar companion can increase food portions and the food tends to be high-calorie in men (Baker et al, 2019;Otterbring, 2018), women eat more than men (Remick, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This activity influences their food choices and is a significant predictor of eating behavior 18 . A negative relationship was found between peer influence and healthy food choices, meaning the greater the peer influence, the lower the likelihood that adolescents will choose healthy foods 50 . Studies show that peers can influence the consumption of sweetened beverages and junk food 18 .…”
Section: Relationship Between Variablesmentioning
confidence: 97%